2020
DOI: 10.1016/j.chempr.2020.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst: How Material Chemistry Enables Solar-Driven CO2 Conversion

Abstract: Tingting Kong obtained her PhD degree from Xi'an University of Science and Technology in 2017 and is currently a lecturer at Xi'an Shiyou University. Her research interest focuses on material design for photocatalytic CO 2 conversion. Jingxiang Low obtained his PhD degree from Wuhan University of Technology in 2018 and is currently a postdoctoral fellow at the University of Science and Technology of China (USTC). His research interest focuses on photocatalyst design for CO 2 reduction, nitrogen fixation, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Theo ptimal Co-doped sample,C o 1% @PNC,a chieved the highest yield of 1835 mmol g À1 for the reductive conversion of CO 2 to CO after 15 hofirradiation, as aresult of the cooperative effect between the increased number of active reaction sites and the improved charge carrier separation efficiency( Figure 11 D). Ther esults from ion chromatography, 13 CO 2 isotope labeling experiments,a nd mass spectrometry collectively confirmed that the products of HCOOH and CO are derived from CH 3 OH and CO 2 , respectively.M oreover,t he values of consumed e À /h 1+ during the reaction are close to 1, suggesting ag ood balance between CO 2 reduction and CH 3 OH oxidation.…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…Theo ptimal Co-doped sample,C o 1% @PNC,a chieved the highest yield of 1835 mmol g À1 for the reductive conversion of CO 2 to CO after 15 hofirradiation, as aresult of the cooperative effect between the increased number of active reaction sites and the improved charge carrier separation efficiency( Figure 11 D). Ther esults from ion chromatography, 13 CO 2 isotope labeling experiments,a nd mass spectrometry collectively confirmed that the products of HCOOH and CO are derived from CH 3 OH and CO 2 , respectively.M oreover,t he values of consumed e À /h 1+ during the reaction are close to 1, suggesting ag ood balance between CO 2 reduction and CH 3 OH oxidation.…”
Section: Methodsmentioning
confidence: 66%
“…After the electrons and holes are transferred to the semiconductor surface, electrons will react with acceptors, giving reduction products, while holes can react with donor species to generate oxidation products. However, if electrons and holes are not instantly depleted, they may recombine and energy is lost [3b, 4b, 13] …”
Section: Fundamentals Of Heterogeneous Photocatalytic Co2 Valorizatio...mentioning
confidence: 99%
“…This allows the functional groups (e.g., OH and OOH) on GO surface to bond with the amino group of melamine via hydrogen‐bond interaction, [ 33 ] which could reduce the sublimation of melamine during polycondensation (Figure S2, Supporting Information) thus forming a tight interface between the two components. [ 34 ] Then, the bulk g‐CN/rGO‐FeO x can be briefly obtained by calcinating the melamine/GO‐Fe(OH) 3 precursor at 550 °C in Ar, which induced the formation of g‐CN and the reduction of GO to rGO simultaneously. [ 35 ] Fourth, a top‐down exfoliation of bulk g‐CN in bulk g‐CN/rGO‐FeO x was proceeded to prepare 2D g‐CN/rGO‐FeO x .…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ] However, CO 2 photoreduction efficiency is significantly plagued by the sluggish photo‐generated carriers transfer kinetics and insufficient CO 2 molecule adsorption/activation performance. [ 2 ] Meanwhile, the unclear migration mechanism of electron–hole pairs and the proton‐coupled electron transfer process also obstacle the precise construction of high‐performance materials for CO 2 photoreduction. [ 3 ] To achieve excellent photosynthesis efficiency, enhancing the charge separation and constructing active sites, CO 2 activation is an essential approach.…”
Section: Introductionmentioning
confidence: 99%